Pengaruh Kompetensi Profesional Guru Dan Penggunaa Metode Ummi Terhadap Kemampuan Membaca Al-Qur’an Siwaa: Pengaruh Kompetensi Profesional Guru Dan Penggunaa Metode Ummi - malahayati, Sutikno; Sugiarto, Adam (An Naba, 2020)
The ability to read the Koran is still a serious problem in society, as well as what happens to students, there are many factors that can affect a person's ability to read the Qur'an. Among these factors is the existence of a competent teacher. professional and learning methods that can facilitate students in learning to read the Koran. This type of research used by researchers in this study is quantitative research with multiple regression analysis techniques. The research site is at SDI Child Friendly Depok-West Java. Based on the research results obtained information that; 1) the teacher professional competence variable has a positive and significant effect on students' reading ability of the Al-Qur'an with the Pearson correlation (ry1) correlation coefficient of 0.701. The magnitude of the influence is indicated by the coefficient of determination R2 (R square) = 0.491, which means that the effect of professional competence on students' reading ability of the Al-Qur'an is 49.1% and the remaining 50.1% is determined by other factors. 2) the variable using the Ummi method has a positive and very significant effect on students' reading ability of the Qur'an with the Pearson correlation (ry2) correlation coefficient of 0.795. The magnitude of the influence is indicated by the coefficient of determination R2 (R square) = 0.633, which means that the effect of using the Ummi method on students' reading ability of the Al-Qur'an is 63.3% and the remaining 36.7% is determined by other factors. 3) the variable teacher professional competence and the variable using the ummi method together have a positive and very significant effect on students' reading ability of the Al-Qur'an with the Pearson correlation correlation coefficient (ry1.2) is 0.829. The magnitude of the influence is shown by the coefficient of determination R2 (R square) = 0.688, which means that the effect of the professional competence of teachers and the use of the Ummi method together on students' reading ability of the Koran is 68.8% and the rest is 31.2%. determined by other factors..